Enhancing Edu-Ecotourism in Batudulang Village, Batulanteh District, Sumbawa Regency: Strategies and Potential Development - Ananda Putri, Widya; Suteja, I Wayan; Abdullah, Ajuar (Advances in Tourism Studies, 2023)
This study aims to describe the potential of edu-ecotourism and formulate strategies for developing edu-ecotourism in Batudulang Village, Batulanteh District, Sumbawa Regency. This research is descriptive and qualitative. The study starts by identifying existing potential and analyzing supporting and inhibiting factors, followed by using the SOAR technique to identify opportunities. Data collection techniques include field observations, interviews, and documentation, with informants selected through purposive samplings, such as the Head of Batulanteh Production Forest Management Center, the Secretary of Batudulang Village, the Batudulang Tourism Awareness Group, and the Head of Village-Owned Enterprises. The strategy for edu-ecotourism development is based on the SOAR analysis, which focuses on developing all existing potentials, including natural resources such as biodiversity (flora and fauna) and the beauty of the landscape, as well as the natural topography potential of the area and the local community's culture. All these potentials can be packaged into one edu-ecotourism package, taking into account market segmentation.